Regional social planning for childhood in Italy (Journal of Comparative Social Work, 2013)
The objective of the study is that of a planning document analysis of social and health-care policies developed by Italian regional governments during the period from 2007-2010, in order to identify a context analysis, objectives, actions relating to children and to verify the presence of an orientation to child’s rights.The document analysis concerning regional programmes for children was conducted employing a programme theory approach. This approach is used in order to compare programmes that, while very different in breadth and general scope, are nevertheless intervention plans for children, with the purpose of identifying the presence of common models and classifying any resulting differences.